ANALISIS KOMPETENSI, BUDAYA ORGANISASI, STRES KERJA DAN KINERJA STUDI KASUS PADA PEGAWAI KANTOR BERSAMA SAMSAT PURWOREJO - Arry Harmoko; Nur Wening (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
The aims of this study is to analyze competency, organizational culture, work stress and employee performance at the SAMSAT Purworejo Shared Office (2019). The type of this study is categorized quantitative descriptive with descriptive statistical analysis method that is calculating mean and mode. This study was conducted at the SAMSAT Purworejo Shared Office with 30 (thirty) employee.The results of this study indicate that the competence of employees at the SAMSAT Purworejo Shared Office is very good, although there are still errors in work due to lack of employee task skills. The organizational culture there has been good, but in the organizational decision-making process it has not involved all employees and only a few employees think that this work is competitive. The work stress of employees is still relatively low, but the dimensions of work stress caused by work conditions that results in physical and mental fatigue of employees due to excessive workload has a highest mark. The performance of employees is very good, but there are still many employees who have a tendency not to complete their tasks independently. Some alternative recommendations which can be applied at SAMSAT Purworejo Shared Office to improve employee competency are to build a better organizational culture, minimize employee work stress and improve employee performance to achieve organizational goals that is to optimize motor vehicle tax receipts.Keywords                     :           Competence, Organizational Culture, Work Stress, Performance